Bridging disciplinary aesthetics: when mathematics meets art through educational technology - Karavakou, Myrto; Kynigos, Chronis; Sinclair, Nathalie (Frontiers in Education, 2023)
In this article, we discuss the way students’ aesthetic experiences can shape the learning of mathematics at higher school levels. We designed a learning environment based on three main design principles: 1) Mathematics as Artistic, where mathematics is used for open artistic creation; 2) Aesthetically rich mathematical experiences, that enable students to appreciate mathematical beauty and aesthetic experiences of wondering, imagining, conjecturing, testing, discovering, making connections, problem posing and solving; 3) Constructionism, where mathematical sense making is interwoven with constructing a personally meaningful digital artefact. Two students of the 11th grade participated in a case study, where they used expressive digital resources for representing, manipulating and exploring periodic functions in order to create an animated artefact based on a piece of music. The collected data fed the formation of a theoretical model for analysing students’ aesthetically driven mathematical meaning making, in an attempt to structure existing theoretical concepts around mathematical aesthetics in education. A part of the analysis of students’ aesthetic experiences based on this model is presented and further reflectively discussed with respect to the prospect of an aesthetically oriented curriculum reform.